2007
DOI: 10.1111/j.1365-2036.2007.03541.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: gastrointestinal bleeding due to interaction between selective serotonin uptake inhibitors and non‐steroidal anti‐inflammatory drugs

Abstract: SUMMARY BackgroundSelective serotonin reuptake inhibitors (SSRIs) have been associated with upper gastrointestinal haemorrhage (UGIH) but the magnitude and characteristics of this reaction and possible interaction with concurrent Non-Steroidal Anti-Inflammatory Drug (NSAID) therapy are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(78 citation statements)
references
References 18 publications
(23 reference statements)
2
66
1
7
Order By: Relevance
“…Four of the articles included in the present study 2,3,9,10) reported a >2-times higher risk of UGIH with combination use vs. SSRIs alone, whereas none of the six articles reported the same risk increase for the use of NSAIDs alone. This suggests that the risk of UGIH with combination use of SSRIs and NSAIDs is higher than the additive effect of each type of drug alone (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Four of the articles included in the present study 2,3,9,10) reported a >2-times higher risk of UGIH with combination use vs. SSRIs alone, whereas none of the six articles reported the same risk increase for the use of NSAIDs alone. This suggests that the risk of UGIH with combination use of SSRIs and NSAIDs is higher than the additive effect of each type of drug alone (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…However, the conclusions of past studies varied; some concluded that the risk was not increased with combination use, 4,8,12,13) whereas others concluded that risk was increased [1][2][3][9][10][11][14][15][16][17] compared to use of SSRIs or NSAIDs alone.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is well established that the risk of association between NSAIDs and peptic disease and its complications, also depends on other risk factors inherent to the patient, including advanced age, presence of co-morbidities, concomitant drugs, smoking and a history of peptic ulcer disease and bleeding (126,205) . The risk of NSAIDs causing ulceration and bleeding also varies with the toxicity, dosage and duration of the medication used (185) .…”
Section: Statement 24mentioning
confidence: 99%
“…Csoka, Bahrick & Mehtonen (2008) report that sexual dysfunction can continue even after drugs are discontinued. Serotonin transporters, the target for the SSRIs, are also found on blood platelets and SSRIs are associated with risk of bleeding ulcers (Loke, Trivedi, and Singh, 2008;Serebruany, 2006) and stroke (Wu, Wang, Cheng, & Gau, 2011).…”
Section: Adverse Effects Short Termmentioning
confidence: 99%